2014
DOI: 10.1111/1471-0528.13042
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss in pregnancy and cardiometabolic profile in childhood: findings from a longitudinal birth cohort

Abstract: Objective To investigate the consequences of weight loss in pregnancy on pregnancy outcomes and cardiometabolic profile in childhood.Design Prospective birth cohort (ABCD study). Population 7818 pregnant women were included, of which 3165 consented to having their children examined at 5-6 years of age. In 1956 children fasting capillary blood samples were also taken.Methods At antenatal booking, women answered questions about their pregnancy and whether they suffered from severe weight loss (SWL; >5 kg). Pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 47 publications
1
29
2
2
Order By: Relevance
“…Moreover, their offspring displayed normoweight at birth and during lactation in a sex and diet-independent manner. This finding is in agreement with previous studies in humans, which demonstrated that offspring exposed to famine or hyperemesis gravidarum in the first part of pregnancy did not show lower birth weight (Roseboom et al, 2006; Grooten et al, 2015). Similarly, animal studies documented normoweight at birth when the early pregnancy was conducted under caloric restriction (Cleal et al, 2007; Palou et al, 2010; Poore et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, their offspring displayed normoweight at birth and during lactation in a sex and diet-independent manner. This finding is in agreement with previous studies in humans, which demonstrated that offspring exposed to famine or hyperemesis gravidarum in the first part of pregnancy did not show lower birth weight (Roseboom et al, 2006; Grooten et al, 2015). Similarly, animal studies documented normoweight at birth when the early pregnancy was conducted under caloric restriction (Cleal et al, 2007; Palou et al, 2010; Poore et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Kandou Hospital, Manado, Indonesia among them 1 patient died due to Wernicke. 11,12 The main objective of this study was to determine the relationship between BMI and β-HCG levels with hyperemesis gravidarum.…”
Section: Introductionmentioning
confidence: 99%
“…reported that healthy prepubertal adolescents born to severely hyperemetic mothers (defined as hospitalisation for HG with electrolyte abnormalities) had reduced insulin sensitivity. Grooten et al . showed that offspring born to mothers who suffered from severe weight loss (>5 kg weight loss) during pregnancy, usually occurring as a manifestation of HG, have higher diastolic blood pressure at the age of 5 years in comparison with offspring born to mothers who did not suffer from severe weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…and Grooten et al. have prompted us to further investigate long‐term consequences of HG on offspring health . The Northern Finland Birth Cohort 1986 (NFBC1986) is a large, prospective population‐based cohort with long‐term follow‐up and information about HG during pregnancy.…”
Section: Introductionmentioning
confidence: 99%